ANALYSIS OF ORGANIZATIONAL CULTURE CASE STUDY: SHARED SERVICE CENTER UNIT PELINDO III (The Indonesian Journal of Business Administration, 2019)
The purpose of this study is to analyze the current organizational culture in the SSC unit and provide cultural recommendations as expected by employees in the next 2 years. Data collection is done using a questionnaire Organizational Culture Assessment Instrument (OCAI) that is distributed to all employees and leaders in the SSC unit. The purpose of the OCAI is to assess six key organizational cultures from the concept of Competing Value Framework (CVF). The results of the assessment indicate that the overall dimension in the SSC unit is currently dominated by clan culture, as well as the overall dimensions expected in the SSC unit are still dominated by clan culture that emphasizes family atmosphere and participation. From the culture of the adhocracy there was a considerable gap from the current and expected culture. This means that respondents expect organizations in the future to be more innovative and enthusiastic in facing new challenges. For the hierarchy culture and the expected market tends to decline than at present. The final results of the overall cultural analysis show that there is no significant gap in the current and expected organizational culture, which is still dominated by clan culture. This means that overall the SSC unit is more internal focus than external focus.Based on these results, plans for improvements that can be made at the SSC unit include minimizing miss communication with routine morning briefings, increasing competence with training related to work and supporters, and workshops to the region for external improvement.Keywords:  adhocracy, clan, CVF, hierarchy,  market, OCAI, SSC